Impact of Surface Treatment of Flax Fibers on Tensile Mechanical Properties Accompanied by a Statistical Study - Bedjaoui, Azzedine; Belaadi, Ahmed; Amroune, Salah; Madi, Belgacem (International Journal of Integrated Engineering, 2019)
In this work, a surface treatment with sodium bicarbonate (NaHCO3) at different concentrations of 4 and 8% is applied to the surface of the flax fiber for a period of 80 hours at room temperature. The purpose of this study is to observe the effect of different treatment processes on the flax fiber, i.e. on its mechanical properties such as: stress and strain at break and Young’s modulus. A major test campaign of more than 240 tests is carried out. Due to the variability of the plant fibers, more than 80 samples were tested for each group at a gauge length (GL = 10 mm). The results of the quasi-static tensile tests have a large dispersion which makes it possible to measure the degree of variability in the stress and strain deformation and the Young’s modulus of the fiber. This degree of variability has been studied by means and statistical tools such as the Weibull distribution at two.